2017
DOI: 10.5796/electrochemistry.85.77
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Various Cathode Materials against Li<sub>6.25</sub>Al<sub>0.25</sub>La<sub>3</sub>Zr<sub>2</sub>O<sub>12</sub> Electrolyte

Abstract: Thermal stability of LiCoO 2 , LiMn 2 O 4 and LiFePO 4 with Li 6.25 Al 0.25 La 3 Zr 2 O 12 (Al-LLZ) solid electrolyte was investigated at 300-800°C. In the case of LiCoO 2 /Al-LLZ mixture, the XRD patterns and charge-discharge behavior did not change after the heat treatment at 800°C. In contrast, the formation of impurities and degradation of cathode performance were observed for LiMn 2 O 4 /Al-LLZ mixture and LiFePO 4 /Al-LLZ mixture. The decomposition of Al-LLZ and the formation of some impurities were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…364−366 While hightemperature sintering can densify pellets, it can also cause unwanted reactions between the cathode and SE, resulting in high interfacial resistance and poor cell performance. 367,368 The addition of an ionic-conductive low-melting-temperature binder such as Li 3 BO 3 has been shown to improve the cathode/SE contact and reduce the interfacial resistance. 369 Similarly, polymers such as poly(ethylene oxide) (PEO) have been used to improve the interfacial contact in oxide-SE-based composite cathodes.…”
Section: Composite Electrode Morphologymentioning
confidence: 99%
“…364−366 While hightemperature sintering can densify pellets, it can also cause unwanted reactions between the cathode and SE, resulting in high interfacial resistance and poor cell performance. 367,368 The addition of an ionic-conductive low-melting-temperature binder such as Li 3 BO 3 has been shown to improve the cathode/SE contact and reduce the interfacial resistance. 369 Similarly, polymers such as poly(ethylene oxide) (PEO) have been used to improve the interfacial contact in oxide-SE-based composite cathodes.…”
Section: Composite Electrode Morphologymentioning
confidence: 99%
“…37 Furthermore, this approach would be exclusive to these phases and would not apply for many other oxide cathodes because of their higher reactivity with LLZO. 38 For instance, a pellet-based compatibility study 39 40,41 Sintering additives can be used to facilitate the particle interconnection and densification of the cathode and electrolyte interface at reduced processing temperature, as shown in Fig. 1a(ii).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a number of Table I. decomposition materials such as La 2 Zr 2 O 7 , La 2 O 3 , La 3 TaO 7 , TiO 2 , and LaMnO 3 form and are detrimental to interfacial impedance after fabrication. 146,150 Lower temperature densification and processing steps could be a valuable method to mitigate these effects. 187 Broadly speaking, with the exception of thin film cathodes all reports of full cell architectures utilize lower active material electrode loading than state-of-the-art liquid cells.…”
mentioning
confidence: 99%